2008
DOI: 10.1037/0021-843x.117.2.314
|View full text |Cite
|
Sign up to set email alerts
|

Ruminative self-focus and negative affect: An experience sampling study.

Abstract: The authors conducted an experience sampling study to investigate the relationship between momentary ruminative self-focus and negative affect. Ninety-three adults recorded these variables at quasi-random intervals 8 times daily for 1 week. Scores on questionnaire measures of dispositional rumination were associated with mean levels of momentary ruminative self-focus over the experience sampling week. Concurrently, momentary ruminative self-focus was positively associated with negative affect. Cross-lagged ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
361
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 358 publications
(414 citation statements)
references
References 53 publications
40
361
3
2
Order By: Relevance
“…[1][2][3] Phenomenological dissimilarities between these constructs were not analyzed, and they were not classified hierarchically. [3][4][5][6][7] All were ontologically identical, equivalent and horizontally distributed, and there was no definition of hierarchical differences between them. [1][2][3][4][5][6][7][8][9] These characteristics may have resulted in misconceptions that, in turn, led to theoretical disagreement, erroneous theoretical models and flawed interpretations of results.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3] Phenomenological dissimilarities between these constructs were not analyzed, and they were not classified hierarchically. [3][4][5][6][7] All were ontologically identical, equivalent and horizontally distributed, and there was no definition of hierarchical differences between them. [1][2][3][4][5][6][7][8][9] These characteristics may have resulted in misconceptions that, in turn, led to theoretical disagreement, erroneous theoretical models and flawed interpretations of results.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6][7] All were ontologically identical, equivalent and horizontally distributed, and there was no definition of hierarchical differences between them. [1][2][3][4][5][6][7][8][9] These characteristics may have resulted in misconceptions that, in turn, led to theoretical disagreement, erroneous theoretical models and flawed interpretations of results. [3][4][5][6][7]17,20,21,[23][24][25] The analysis of studies in our final sample suggested the existence of causal links between neurophysiological and neuroanatomical findings and CR.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations